2006
DOI: 10.1080/03043790600567035
|View full text |Cite
|
Sign up to set email alerts
|

Creating a bridge to simulate simultaneous engineering experiences for senior undergraduate students

Abstract: Launching new or improved products to the market typically involves extensive collaboration within and beyond the enterprise. Succeeding in a customer-driven market economy demands the practice of simultaneous engineering. The standard engineering or engineering technology curricula continue to make efforts in providing students with opportunities to engage in real-life projects that simulate simultaneous engineering. However, the educational community as a whole has much to implement in this area. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In addition, faculty oversight was discussed as critical in shaping teaching and learning in engineering education (Marchese et al, 2001). Moreover, the presence of faculty was found as essential in fostering faculty and student collaboration and mentor–mentee relationships (Otieno et al, 2006; Teller & Gates, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, faculty oversight was discussed as critical in shaping teaching and learning in engineering education (Marchese et al, 2001). Moreover, the presence of faculty was found as essential in fostering faculty and student collaboration and mentor–mentee relationships (Otieno et al, 2006; Teller & Gates, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…More examples of students' performance checks included a working assessment of project design (Otieno et al, 2006), post-quiz, and post-design (Clark & Dickerson, 2019) results. There was also a direct assessment check (course design notebook, oral presentations, etc.)…”
Section: Student Performance At the Core Of Experiential Learning Eva...mentioning
confidence: 99%
“…Felder et al (2011) observed that outcomes-based program accreditation increasingly requires changes in the traditional model of engineering education and delivery. Researchers have pointed to the importance of collaborative work environments and multidisciplinary teams (Bannerot et al 2010;Chou et al 2007;Fortenberry 2011;Gruenther et al 2009;Otieno et al 2006;Patel et al 2012;Zhao 2011). Hanna and Sullivan (2005) reported on their institution's effort to bridge the gap between academics and practice in senior design.…”
Section: Incorporation Of the Tuscaloosa Forward Initiative Into The University Senior Design Studiomentioning
confidence: 99%